2020
DOI: 10.3390/nano10122573
|View full text |Cite
|
Sign up to set email alerts
|

Ipriflavone-Loaded Mesoporous Nanospheres with Potential Applications for Periodontal Treatment

Abstract: The incorporation and effects of hollow mesoporous nanospheres in the system SiO2–CaO (nanoMBGs) containing ipriflavone (IP), a synthetic isoflavone that prevents osteoporosis, were evaluated. Due to their superior porosity and capability to host drugs, these nanoparticles are designed as a potential alternative to conventional bioactive glasses for the treatment of periodontal defects. To identify the endocytic mechanisms by which these nanospheres are incorporated within the MC3T3-E1 cells, five inhibitors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 51 publications
5
18
0
Order By: Relevance
“…On the other hand, the present study will allow us to obtain information for the possible future biomedical employment of these mesoporous SiO2-CaO nanospheres in an infection scenario. We have recently shown the utility of this nanomaterial for intracellular drug delivery [34,35]. These previous works have opened the way for future potential profits of this nanomaterial for antifungal delivery by the analysis of the uptake by macrophages of both nanospheres and C. albicans.…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, the present study will allow us to obtain information for the possible future biomedical employment of these mesoporous SiO2-CaO nanospheres in an infection scenario. We have recently shown the utility of this nanomaterial for intracellular drug delivery [34,35]. These previous works have opened the way for future potential profits of this nanomaterial for antifungal delivery by the analysis of the uptake by macrophages of both nanospheres and C. albicans.…”
Section: Introductionmentioning
confidence: 95%
“…Regarding the mineralization analysis, a slight increase of this parameter was also induced by the presence of MBG-75S deposited on the transwell inserts, but this effect was not statistically significant (right panel Figure 4 ). This slight effect on mineralization was probably due to the need of longer differentiation times, as well as the lower precision and sensitivity of this assay, in comparison with ALP measurement, as we have previously observed in other studies with mesoporous nanospheres and MC3T3-E1 pre-osteoblasts [ 53 ]. Several authors have demonstrated the pro-osteogenic effects of MBGs caused by to the release of calcium and silicon ions [ 54 ], and recent research has shown the influence of these kind of biomaterials on pulp cells behavior in vitro, increasing both ALP activity and mineralization in this cell type [ 55 ].…”
Section: Resultsmentioning
confidence: 86%
“…Casarrubios et al [ 54 ] studied mesoporous nanospheres with potential applications for periodontal treatment. The authors evaluated the cytocompatibility of such nanospheres containing ipriflavone (IP), a synthetic isoflavone that prevents osteoporosis.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the secondary outcomes, different authors found that, when human cells were used, BGs induced and/or increased cell viability and proliferation, and stimulated mineralized tissue formation [ 37 , 53 , 55 , 66 , 67 , 72 , 75 ], especially when BG nanoparticles were employed [ 55 , 66 ]. When fibroblast/osteocyte cell lines were utilized, cell viability, cell proliferation, cell differentiation were appreciated [ 60 , 64 , 70 , 71 ], in particular with mesoporous BG nanospheres/nanoparticles [ 54 , 68 ]. Some studies detected specific cell factors involved in the osteoinduction response [ 37 , 56 , 59 ], while BGs in membranes promoted healing [ 64 , 65 , 66 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%